Solar Scholar: A Thin-Film Solar Bag for Sustainable Energy Generation in Academic and Professional Mobility - Oli, Arjun; Poudel, Yam Krishna (Journal of Engineering Issues and Solutions, 2025)
This research focuses on the development of the solar backpack along with the real data simulation extracted from the Jumla district. The increasing demand for portable renewable energy solutions has stimulated innovations in wearable solar technology. This innovation provides a reliable and portable solution for energy generation, yielding a significant cumulative output that effectively satisfies the energy needs of personal devices over extended periods. This study presents the design, development, and performance evaluation of a solar-powered bag integrated with lightweight thin-film photovoltaic (TFPV) modules for sustainable energy generation during daily mobility. The system exhibits consistent daily performance utilizing realistic hourly solar data from Jumla, demonstrating its practicality for routine applications. This reliability underscores its potential as a viable and marketable product from a business perspective. The findings suggest that such systems could play a significant role in enhancing energy access in remote regions like Jumla, and may warrant greater attention from policymakers in Nepal. It targets students, academics, and professionals. The bag incorporates flexible CIGS or a-Si solar panels (6–10 W output) into its outer surface, paired with a lithium-ion battery (10,000–15,000 mAh) and an MPPT charge controller to optimize energy harvesting. Rigorous testing under varying irradiance conditions demonstrated its ability to provide 2–4 smartphone charges or 1–2 laptop charges daily, with 70% retention in cloudy weather. The system’s efficiency (η ≈ 10–12% for CIGS, 8% for a-Si) and durability were validated through 100+ charge cycles and mechanical stress simulations. By aligning with SDGs 7 (Affordable Energy) and 13 (Climate Action), this innovation bridges the gap between convenience and sustainability, offering a scalable solution for reducing reliance on grid electricity. Challenges include weather dependence and higher initial costs, yet the design proves viable for urban and remote applications.